Evaluating influenza disease burden during the 2008-2009 and 2009-2010 influenza seasons in Mongolia - Pagbajabyn Nymadawa; Rentsengiin Tuul; Hitoshi Oshitani; Luvsanbaldangiin Enkhbaatar; Sosorbaramyn Tsatsral; Tsedenbalyn Naranzul; Baataryn Gantsooj; Ishiin Od; Badarchiin Darmaa; Jigjidsurengiin Od; Taro Kamigaki; Alexanderyn Burmaa; et al. (World Health Organization Regional Office for the Western Pacific, 2011)
It is critical to monitor the incidence and clinical characteristics of influenza and its associated hospitalization to understand influenza disease burden. A disease burden study can inform the prioritization of a public health response. However, little is known about the epidemiology and disease burden of influenza in developing countries, including Mongolia. Thus we performed prospective data and sample collection from patients who visited outpatient clinics with influenza-like illness (ILI) and hospitalized patients with severe acute respiratory infections (SARI) in two sites of Mongolia, Baganuur District of Ulaanbaatar and Selenghe Province, from 2008 to 2010. In total, we examined 350 ILI cases during the 2008-2009 influenza epidemic period and 1723 ILI cases during the 2009-2010 influenza epidemic period. We observed the highest ILI incidence per 1000 population in the one to four year age group in Baganuur and in the under one year age group in Selenghe during both periods. Thirteen SARI cases were positive for seasonal influenza A(H1N1) during the 2008-2009 season and 17 SARI cases were positive for pandemic influenza A(H1N1) 2009 during the 2009-2010 season. Among these cases, 84.6% and 58.8% were children under five years of age, respectively, during the 2008-2009 and 2009-2010 seasons. Taken together, children, especially children under five years, had higher influenza infection incidence and hospitalization rate in Mongolia. Although mortality impact also should be considered, we believe that our findings can be useful in formulating an influenza control strategy during influenza epidemic periods in Mongolia.